Do university students need to master the GSL and AWL words: A psychology word list - Mahmood Safari (Journal of Modern Research in English Language Studies)
University students are mainly advised to master the words in West’s General Service List (GSL) and Coxhead’s Academic Word List (AWL) in order to be able to read their academic texts easily and effectively. However, there are too many words in the two lists and a large number of them seem to be of less frequency in many academic disciplines; moreover, there are many important general and academic words which are missing in the two lists. The present study explored a corpus of psychology texts containing 3.4 million running words to work out the most frequent words used in psychology, a less investigated discipline. The corpus was analyzed by some text analysis software (TextStat and TextAnalys) and a list of 1587 most frequent word families was developed for psychology. The list included general English and academic words and no technical words of psychology. The frequency of GSL and AWL word families was investigated in the corpus to find out the GSL and AWL words highly frequent in psychology texts and also other high frequency words of psychology which are absent in the two lists. The results revealed that 1077 GSL and 95 AWL word families were of low frequency in psychology texts and there were 189 high frequency general and academic words which are absent in the GSL and AWL. The coverage of the developed psychology word list over the corpus was shown to be 2.2% higher than that of GSL plus AWL, although it contained 983 fewer words.